Assessment of the suitability of fetal kidney length measurement for determining gestational age in the third trimester - Walad, Rithvika; Tile, Rajesh; Jamkhandi, Supriya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background Obstetric sonography plays a significant role in the determination of gestational age because of its accuracy and easy reproducibility. Fetal kidney length is claiming to be more accurate in certain situations and emerging as a new parameter. Methods: A cross-sectional study was done on 200 pregnant women from January 2023 to July 2023; third trimester ultrasonography was used to assess the mean fetal kidney length along with the fetal head circumference, femur length, abdominal circumference, and biparietal diameter. Gestational age was calculated from mean fetal kidney length using the nomogram introduced by Cohen L and from multiple biometric parameters using the nomogram by Hadlock FP. The obtained values were then compared with the actual gestational age derived from excellent dates taken as a standard. Results: Fetal kidney length gestational age ranges between 26-40 weeks, with mean 35.5±3.2 (Mean±SD), median 35.9. The correlation of clinical gestational age with fetal kidney length is by r value 0.997. The correlation was best for clinical gestational age with fetal kidney length gestational age. At 40 weeks of clinical gestational age, there were 14 (7%) cases with a mean FKL of 40.09 mm. Conclusions: The correlation between fetal kidney length and clinical gestational age is statistically significant. Therefore, it can be utilized as a dependable parameter for determining gestational age.